2009
DOI: 10.1002/cmmi.273
|View full text |Cite
|
Sign up to set email alerts
|

DCE‐MRI in experimental chronic pancreatitis

Abstract: To assess pancreatic perfusion in experimental chronic pancreatitis (CP) by dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI). DCE MRI on a 1.5 T MR scanner was performed on 21 piglets with the ligation of pancreatic duct. They were divided into four groups based on pathology, including seven normal pigs and seven, three and four piglets with grade I, II and III CP, respectively. The signal intensity measured in the pancreatic body on DCE MRI was plotted against time to create a signal intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Care was taken to exclude spleen hilar blood vessels when drawing the ROIs within the spleen (Figure 1A). Signal intensity time curve (STC, Figure 1B) was derived, and spleen DCE-MRI parameters including time to peak (TTP, Figure 1C), positive enhancement integral (PEI, Figure 1D), maximum slope of increase (MSI, Figure 1E), and maximum slope of decrease (MSD, Figure 1F) were automatically generated by the commercial software based on the curve analysis model [17], [18]. According to this model, TTP was defined as the time from the time point when enhancement could be detectable to the time when the maximum signal intensity (SImax) appeared in the spleen.…”
Section: Methodsmentioning
confidence: 99%
“…Care was taken to exclude spleen hilar blood vessels when drawing the ROIs within the spleen (Figure 1A). Signal intensity time curve (STC, Figure 1B) was derived, and spleen DCE-MRI parameters including time to peak (TTP, Figure 1C), positive enhancement integral (PEI, Figure 1D), maximum slope of increase (MSI, Figure 1E), and maximum slope of decrease (MSD, Figure 1F) were automatically generated by the commercial software based on the curve analysis model [17], [18]. According to this model, TTP was defined as the time from the time point when enhancement could be detectable to the time when the maximum signal intensity (SImax) appeared in the spleen.…”
Section: Methodsmentioning
confidence: 99%
“…The liver DCE‐MRI acquisitions were performed with a modified multiphase fast gradient echo train (FGRET) pulse with the following scanning parameters: repetition time, 14.7 msec; echo time, 3.2 msec; inversion time, 228.2 msec; field of view (FOV), 36–39 × 17–23.4 cm; matrix, 256 × 160; bandwidth, 62.5 kHz; number of signals excitations, 0.5; flip angle, 25°; number of sections, 12; section thickness, 8 mm; slice gap, 1 mm; and acquisition time, 108 seconds. The scanning parameters were referenced from a published article . Additionally, a different FOV used in different piglets was based on their different abdominal sizes; FOV did not differ in the same animal at different timepoints.…”
Section: Methodsmentioning
confidence: 99%
“…b–f) including time of peak (TOP) demonstrated on this curve, time to peak (TTP), maximum slope of increase (MSI), maximum slope of decrease (MSD), and positive enhancement integral (PEI) were automatically generated by the commercial software. According to the published articles , TOP was defined as the time when the maximum signal intensity (SImax) of the STC appeared (Fig. b), and TTP was defined as the time from the timepoint when enhancement could be detectable to the time when SImax appeared in the liver.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have also demonstrated that CP with advanced fibrosis is associated with reduced blood vessel density and decreased pancreatic blood flow [ 8 – 10 ]. Several studies have correlated the grade of CP (degree of fibrosis) with decreased pancreatic blood flow on dynamic contrast-enhanced magnetic resonance imaging (MRI) [ 11 , 12 ]. However, the utility of CEUS in identifying degree of fibrosis in CP, especially early CP, remains unclear.…”
Section: Introductionmentioning
confidence: 99%